The Effect of Digital Zakat and Zakat Education on Muzakki Compliance in Zakat Payment - Judijanto, Loso; Abdullah, Rais; Mas'ut, Mas'ut; Hendratri, Bhaswarendra Guntur (Westscience Press, 2025)
This study investigates the impact of digital zakat platforms and zakat education on muzakki compliance in fulfilling their zakat obligations. Utilizing a quantitative approach, data were collected from 90 respondents through a structured questionnaire using a Likert scale (1–5). The analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings reveal that both digital zakat and zakat education significantly and positively influence compliance, with zakat education exhibiting a stronger impact. Digital zakat enhances accessibility, transparency, and convenience, while zakat education fosters awareness and understanding of zakat's religious and social significance. The study highlights the importance of integrating technology and education to optimize zakat management. These results provide valuable insights for policymakers, zakat institutions, and digital platform developers to enhance compliance and maximize zakat's societal benefits.